The girl with the iron touch - Cross, Kady, 1971- (Cross, Kady, 1971- Steampunk chronicles., 2013)
London, 1897. When mechanical genius Emily is kidnapped by rogue automatons, Finley Jayne and her fellow misfits fear the worst. To save those she cares about, Emily must confront The Machinist's ultimate creation -- an automaton more human than machine.